Overview of research studies on osteoporosis in menopausal women since the last decade - Jyoti Thulkar; Shalini Singh (Wolters Kluwer Medknow Publications, 2015)
Purpose/Introduction: Osteoporosis is a multifactorial and slowly emerging global health problem. The lifetime risk of dying from hip fracture is same as that from breast cancer. One out of three women between age group of 50-60 years in India suffers from osteoporosis. Indian women have an early age of onset of osteoporosis as compared to western counterparts. There is need for early diagnosis, identification of high-risk groups and prevention and treatment of osteoporosis in the Indian context. The aim of this study was to review the literature published in last decade and compare the research in India with that in rest of the world. Materials and Methods: Research articles with key words menopausal, osteoporosis and bone mineral density were searched in Pubmed from January 2004 to December 2013. Articles were categorized according to year, place and objective of the studies. Results: In India more articles were published in year 2010-11 (53.3%), while outside the country a uniform distribution of studies was observed throughout the last decade. Objective of research was screening and diagnosis (36.7%) and risk factor identification (40%) in most of the Indian studies as compared to rest of the world. Research publications on prevention and treatment of osteoporosis are less in India (20%). Conclusion: Research focusing on diagnosis, prognosis, prevention and treatment are needed in India.